2005
DOI: 10.1007/s00253-005-0179-3
|View full text |Cite
|
Sign up to set email alerts
|

The use of microorganisms for the formation of metal nanoparticles and their application

Abstract: Nanomaterials are at the leading edge of the rapidly developing field of nanotechnology. The development of reliable experimental protocols for the synthesis of nanomaterials over a range of chemical compositions, sizes, and high monodispersity is one of the challenging issues in current nanotechnology. In the context of the current drive to develop green technologies in material synthesis, this aspect of nanotechnology is of considerable importance. Biological systems, masters of ambient condition chemistry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
437
0
7

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 944 publications
(446 citation statements)
references
References 57 publications
2
437
0
7
Order By: Relevance
“…The first report on gold nanoparticle synthesis from alfalfa seedlings by GardeaTorresdey et al (2002) demonstrated that Au (III) ions were initially reduced in the solid media to Au (0) by alfalfa plants, and then the metal atoms were absorbed into the plant leading to subsequent reduction. Mandal et al (2006) presumed that the metal ions are initially trapped on the plant cell surface via electrostatic interaction between the ions and negatively charged carboxylate groups present on the cell surface, and that the ions are then reduced by cellular enzymes, leading to the formation of nuclei, which subsequently grow through further reduction of metal ions. In contrast, Sharma et al (2007) showed uptake of high amounts of Au (III) ions by Sesbania drummondii, with subsequent reduction of Au (III) ions to Au (0) inside plant cells or tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The first report on gold nanoparticle synthesis from alfalfa seedlings by GardeaTorresdey et al (2002) demonstrated that Au (III) ions were initially reduced in the solid media to Au (0) by alfalfa plants, and then the metal atoms were absorbed into the plant leading to subsequent reduction. Mandal et al (2006) presumed that the metal ions are initially trapped on the plant cell surface via electrostatic interaction between the ions and negatively charged carboxylate groups present on the cell surface, and that the ions are then reduced by cellular enzymes, leading to the formation of nuclei, which subsequently grow through further reduction of metal ions. In contrast, Sharma et al (2007) showed uptake of high amounts of Au (III) ions by Sesbania drummondii, with subsequent reduction of Au (III) ions to Au (0) inside plant cells or tissues.…”
Section: Discussionmentioning
confidence: 99%
“…http://www.nmletters.org to extract the silver nanoparticles [9]. Filamentous fungi on the other hand are capable of synthesizing the silver nanoparticles extracellularly but the downstream processing and the biomass handling make them difficult [10][11][12].…”
mentioning
confidence: 99%
“…It is thought that surface of algal cells, possibly via electrostatic interaction between the ions and negatively charged carboxylate groups present in the cell surface. Thereafter, the ions are reduced by the enzymes, leading to the formation of nuclei, which subsequently grow through the further reduction of metal ions and accumulation of these nuclei (Mandal et al, 2006). TEM images of the different silver NPs reveal that the silver NPs seem to be spherical in morphology and well distributed with an average size of 20.8±4.0; 8.2±3.0 and 8.8±2.0 nm for S. platensis and C. vulgaris as well as Sc.…”
Section: Discussionmentioning
confidence: 99%